IMPROVING STUDENTS READING ABILITY BY USING WEBTOON AT SEVENTH GRADE OF MTS DDI KULO - Lababa, Lababa (Uniqbu Journal of Social Sciences, 2022)
The objective of the article are to find out whether or not the use of Webtoon can improve students’ reading ability at seventh grade of MTS DDI Kulo in academic year 2017/2018. This article employed pre-experimental method with one group pre-test and post-test design. The population was the seventh year student (VII) of MTS DDI Kulo in academic years 2018-2017, it consisted of one class. The total number of population was 40 students’ and whole class was taken as sample by using random cluster sampling technique, class VII (29) Was a chosen as sample. The article instrument were multiple choice. The result of this article showed that the pre-test got the mean score (60) while the post-test got mean score (80). This showed that there was significant difference between pre-test and post –test. The result of the P-value (0,000) was lower α ( 0.05). This means that H1 was accepted. Based on the result, the researcher concluded that teaching Reading by using webtoon improves students reading ability at seventh year students of MTS DDI Kulo.